‘n Beradingsprogram vir kinders wat ‘n trauma beleef het (Afrikaans) - Jacobs, L.J. (University of Pretoria, 2013)
Dissertation (MEd (Learning Support, Guidance and Counselling))--University of Pretoria, 2006.